A HOLISTIC APPROACH IN THE NURSING CARE OFPERSONS WITH DEPRESSION - Zubac, Danica; Dimoski, Zvonko; Pavlović Jugović, Katarina; Mitrović, Dragica; Jovanović, Vesna (HEALTH CARE, 2024)
Depression is a mood disorder characterized by the presence of unexplained sadness, loneliness, and hopelessness. In order to ensure the highest possible quality of care for patients with depression, a holistic approach is applied. The aim of this review was to assess the importance of applying a holistic approach in the nursing care of patients with depression, as well as nursing activities in the destigmatization of these persons. This review includes research published in English, based on the search of the PUBMED database, for the last 20 years, using the following keywords: holistic approach, mental health, depression, health care, nurses. A large number of o studies deal with a holistic approach in the nursing care of people with depression. The holistic approach represents the observation of the being as a whole, care for the human body, mind and spirit. The care needs of persons with depression are numerous, and therefore, it is important to plan and systematically assess their needs from a holistic aspect in order to plan the most adequate interventions to solve or reduce them. A special emphasis is placed on improving the lifestyle – healthy diet, good sleep, daily physical activity, as well as on improving social life aspects through socializing and organizing various activities. Nurses make a significant contribution to destigmatization, by educating the population, especially young people. Nurses should focus their activities on applying the holistic approach in the health care and treatment of patients with depression, accepting the documenting of health care process as a standard method in nurses' work which ensures the complete implementation of a holistic approach to health care, conducting research on the significance of implementing a holistic approach in the professional nurses' work, educating the future personnel, destigmatizing the patients with depression, as well as on mental health promotion.
Keywords: holistic approach, mental health, depression, nursing care, nurses